Community Empowerment Through Socialization and Assistance in 3R (Reduce, Reuse, Recycle) Based on Waste Management: Pemberdayaan Masyarakat Melalui Sosialisasi dan Pendampingan Pengelolaan Sampah Berbasis 3R (Reduce, Reuse, Recycle) - Angga, La Ode; Akyuwen, Rory Jeff; Hoiriah, Hoiriah; Asolomudin, Asolomudin; Labetubun, Muchtar Anshary Hamid; Fataruba, Sabri (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The waste problem in Ambon City is a crucial issue that has not been resolved, characterized by an increase in the volume of daily waste that is not balanced by adequate management capacity, as well as environmental pollution on the coast of Ambon Bay, of the 220 tons of waste produced every day, only about 185 tons are accommodated in landfills, the rest is thrown into the sea or scattered. Limited facilities, infrastructure, and public knowledge about waste management are triggers for waste emergencies. Purposes of The Devotion: This service activity aims to form an economically and socially independent society, create a healthy environment free of waste, and improve skills in waste management. Method of The Devotion: The methods used include the preparation stage, implementation (socialization of the 'Bersama Family' program, counseling, assistance in waste sorting, creativity training in processing waste into products with selling value, as well as monitoring and evaluation), and reporting. The approach applied is training, counseling, socialization, and mentoring based on the 3R (Reduce, Reuse, Recycle) paradigm. Results Main Findings of the Devotion: Community-based waste management with the 3R paradigm has proven effective. Socialization and mentoring activities in Silale showed positive achievements with high participation (55 people) and increased material understanding. There were initial initiatives in independent waste management, as well as the formation of a simple model of waste banks and waste bank communities which were positively welcomed. This activity is relevant and effective in increasing community awareness and skills, opening up opportunities for the formation of new community-based institutions, and contributing to reducing waste generation and improving welfare.